PENGUATAN PENDAMPING PROSES PRODUK HALAL (PPH) UNTUK MAHASISWA UIN DATOKARAMA PALU - Pratiwi, indri; Rabiatul Adawiyah, Siti; Nurinayah, Nurinayah; Syarief Hidayatullah, Muhammad (ABIDUMASY, 2024)
The need for halal products is increasing among Indonesian society, which is predominantly Muslim. The government, through the Halal Product Guarantee Agency (BPJPH), is responding to this challenge with a halal certification process through a self-declared program. The program to accelerate the halal certification process requires the role of companion of Halal Product Process (PPH). Since 2022, UIN Datokarama Palu, through the Datokarama Halal Center, is committed to carrying out training activities of companion of halal product process for people from various circles, including students. The activities did not end with training but continued with activities to strengthen the companion of halal product process. The aim of this activity is to provide strengthening for the companion in PPH who have passed the training.The method of implementing activities uses the forum group discussion (FGD) method and the simulation method. The results of the activity showed that the Strengthening the companion of Halal Product Process from UIN Datokarama Palu students went well. Participants have understood the use of the Sihalal application. In addition, 95% of participants have a strong desire to learn to improve their halal accompaniment skills so they can help Business Owner (PU) to register businesses that require a Halal Certificate (SH). This can be seen from the positive response from participants in the training until the end of the activity. Through this Strengthening the companion of Halal Product Process activities, it is hoped that students will become more active and initiative in helping small and micro businesses to obtain halal certificates.